International Monetary Fund Annual Report 1982. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1982)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1982. The report highlights that the world economic developments during 1981 and the first half of 1982 were marked by signs of progress in the difficult fight against inflation. Despite this favorable aspect, the general situation in mid-1982 remained troublesome, posing major challenges to economic policy for both national governments and international institutions. Throughout 1981 and the first half of 1982, abatement of inflation remained the prime objective of financial policies in the industrial countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet